Cancer treatment and survivorship statistics, 2016. (2nd June 2016) - Miller, Kimberly D.; Siegel, Rebecca L.; Lin, Chun Chieh; Mariotto, Angela B.; Kramer, Joan L.; Rowland, Julia H.; Stein, Kevin D.; Alteri, Rick; Jemal, Ahmedin
Abstract: The number of cancer survivors continues to increase because of both advances in early detection and treatment and the aging and growth of the population. For the public health community to better serve these survivors, the American Cancer Society and the National Cancer Institute collaborate to estimate the number of current and future cancer survivors using data from the Surveillance, Epidemiology, and End Results cancer registries. In addition, current treatment patterns for the most prevalent cancer types are presented based on information in the National Cancer Data Base and treatment‐related side effects are briefly described. More than 15.5 million Americans with a history of cancer were alive on January 1, 2016, and this number is projected to reach more than 20 million by January 1, 2026. The 3 most prevalent cancers are prostate (3, 306, 760), colon and rectum (724, 690), and melanoma (614, 460) among males and breast (3, 560, 570), uterine corpus (757, 190), and colon and rectum (727, 350) among females. More than one‐half (56%) of survivors were diagnosed within the past 10 years, and almost one‐half (47%) are aged 70 years or older. People with a history of cancer have unique medical and psychosocial needs that require proactive assessment and management by primary care providers. Although there are a growing number of tools that can assist patients, caregivers, and clinicians in navigating the various phases of cancer survivorship, further evidence‐based resources are needed to optimize care.CA Cancer J Clin 2016;66:271‐289. © 2016 American Cancer Society